Chemical Profiling of Essential Oils from Main Culinary Plants—Bay (Laurus nobilis L.) and Rosemary (Rosmarinus officinalis L.) from Montenegro - Zoran S. Ilić; Ljiljana Stanojević; Lidija Milenković; Ljubomir Šunić; Aleksandra Milenković; Jelena Stanojević; Dragan Cvetković (Horticulturae)
The aim of the research was to determine the yield, chemical composition and free radical-scavenging activity of the essential oils (EOs) in the leaves and fruit of wild-grown bay (Laurus nobilis L.) and rosemary(Rosmarinus officinalis L.)from the Montenegro coast. The bay essential oil (BEO) yield was 0.88% in fruit and 2.65% in the leaves. The rosemary essential oil (REO) yield was 1.30%. BEOs obtained from the leaves and fruit display different compositions. Fifty components were identified in leaf BEO, with 1,8-cineole (39.4%), linalool (13.9%), α-terpinyl acetate (11.2%), sabinene (6.7%) and methyl eugenol (5.7%) being the most abundant ones. Fifty-five components were isolated from fruit BEO, with 1,8-cineole (34.2%), α-pinene (6.6%), sabinene (6.1%) and β-bisabolene (5.8%) being the main components. Twenty-seven components were identified in leaf REO, with the main components being camphor (31.9%), borneol (12.2%), 1,8-cineole (11.3%) and myrcene (10.7%). The BEOs isolated from leaves (EC50 value of 1.43 mg/mL) and fruit (EC50 value of 3.74 mg/mL) showed stronger antioxidant activity than REO (EC50 value of 5.00 mg/mL) during an incubation time of 20 min. The results obtained for the bay and rosemary EOs from Montenegro highlight their potential not only for culinary purposes but also as a source of antioxidants and for use in the food and pharmaceutical industries.